2018
DOI: 10.1130/g45415.1
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap: 40Ar/39Ar dating of volcanic eruptions from the ‘Age of Discovery’

Abstract: Many volcanoes worldwide still have poorly resolved eruption histories, with the date of the last eruption often undetermined. One such example is Ascension Island, where the timing of the last eruption, and consequently, the activity status of the volcano, is unclear. Here, we use the 40 Ar/ 39 Ar dating technique to resolve ages of the three youngest lava flows on the island, which are hawaiites and mugearite with 1.5-1.9 wt% K2O. In dating these lavas, we provide the first evidence of Holocene volcanic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Volcanism began on the sea bed -6 Myr ago, and subaerial volcanism has occurred from ~1 Ma to present (Kar et al, 1998;Minshull et al, 2010;Paulick et al, 2010;Jicha et al, 2013;Preece et al, 2016). The most recent eruption at Ascension Island has been dated using 40 Ar-39 Ar dating to 0.51 ± 0.18 ka (Preece et al, 2018) -with no evidence for pauses in eruptive activity of greater than 130 kyr throughout the 1 million years of subaerial volcanism (Jicha et al, 2013).…”
Section: Ascension Islandmentioning
confidence: 99%
“…Volcanism began on the sea bed -6 Myr ago, and subaerial volcanism has occurred from ~1 Ma to present (Kar et al, 1998;Minshull et al, 2010;Paulick et al, 2010;Jicha et al, 2013;Preece et al, 2016). The most recent eruption at Ascension Island has been dated using 40 Ar-39 Ar dating to 0.51 ± 0.18 ka (Preece et al, 2018) -with no evidence for pauses in eruptive activity of greater than 130 kyr throughout the 1 million years of subaerial volcanism (Jicha et al, 2013).…”
Section: Ascension Islandmentioning
confidence: 99%
“…Volcanism began 5-6 Ma [Klingelhöfer et al 2001;Minshull et al 2010], but subaerial volcanism began only at~1 Ma (from Ar-Ar dating, [Jicha et al 2013]). Recent studies have shown that the island is still active, with the most recent eruption dated to 0.51˘0.18 ka [Preece et al 2018]. Ascension Island volcanism is the product of a transitional to mildly alkaline magmatic series of olivine basalt -hawaiite -mugearite -benmoreite -trachyte -rhyolite.…”
Section: Magmatism At Ascension Islandmentioning
confidence: 99%
“…The ∼ 3,800 km 3 volcanic edifice rises ∼ 4 km from the sea floor, with only 1% of its total volume exposed subaerially (Harris, 1983;Klingelhöfer et al, 2001). Submarine volcanism is believed to have begun at ∼ 6 to 7 Ma, with the edifice becoming subaerial at ∼ 1.09 Ma (Jicha et al, 2013;Preece et al, 2016Preece et al, , 2018; Figure 2). The geology of the island is well described (e.g., Daly, 1925;Darwin, 1845;Atkins et al, 1964;Nielson and Sibbett, 1996;Weaver et al, 1996;Kar et al, 1998).…”
Section: Ascensionmentioning
confidence: 99%
“…Mafic volcanic rocks are found across the island, whereas felsic eruptive products are found in two main areas; the Central Felsic Complex which forms the high ground in the island's center, and the Eastern Felsic Complex. There has been no historical volcanic activity on the island, although the youngest lava flows have recently been reliably dated at < 1 ka (Preece et al, 2018).…”
Section: Ascensionmentioning
confidence: 99%